Statistics of Conditional Fluid Velocity in the Corrugated Flamelets Regime of Turbulent Premixed Combustion: A Direct Numerical Simulation Study - Nilanjan Chakraborty; Andrei N. Lipatnikov (Journal of Combustion)
The statistics of mean fluid velocity components conditional in unburned reactants and fully burned products in the context of Reynolds Averaged Navier Stokes (RANS) simulations have been studied using a Direct Numerical Simulation database of statistically planar turbulent premixed flame representing the corrugated flamelets regime combustion. Expressions for conditional mean velocity and conditional velocity correlations which are derived based on a presumed bimodal probability density function of reaction progress variable for unity Lewis number flames are assessed in this study with respect to the corresponding quantities extracted from DNS data. In particular, conditional surface averaged velocities (ui)¯Rs and the velocity correlations (uiu)j¯Rs in the unburned reactants are demonstrated to be effectively modelled by the unconditional velocities (ui)¯R and velocity correlations (uiuj)¯R, respectively, for the major part of turbulent flame brush with the exception of the leading edge. By contrast, conditional surface averaged velocities (ui)¯Ps and the velocity correlations (uiu)j¯Ps in fully burned products are shown to be markedly different from the unconditional velocities (ui)¯P and velocity correlations (uiuj)¯P, respectively.